Complex replacement patterns in garnets from Bergen Arcs eclogites: A combined EBSD and analytical TEM study - Pollok, K.; Lloyd, G.; Austrheim, H.; Putnis, Andrew (Elsevier GmbH - Urban und Fischer, 2008)
Eclogite-facies rocks within the Bergen Arcs, western Norway, have formed from granulites along shear zones and fluid pathways. Garnets that were inherited from granulite facies protoliths show different types of replacement patterns due to an incomplete eclogitisation process including concentric rim zoning, zoning along vein fillings and inclusion trails, and zoning bands without inclusions. The interfacial part between the granulitic core and the eclogitic rim of garnet as well as the microstructure of other relevant minerals (omphacite, plagioclase) has been analysed using analytical transmission electron microscopy (ATEM). In garnet, the interface is characterised by gradual changes in composition from Xalm=0.31, Xpyr=0.50 to Xalm=0.54, and Xpyr=0.25 within ˜20 µm and exhibits no distinct change in microstructure. Granulitic plagioclase shows exsolution lamellae of the Bøggild intergrowth. In omphacite, anti-phase domains (APDs) which potentially record the temperature of cation ordering after mineral growth have been observed and their size suggest eclogitisation at 600-700 °C. The electron backscatter diffraction (EBSD) analysis revealed that the lattice orientation of the granulitic feldspar is basically unrelated to tectonic axes whereas newly formed eclogitic minerals omphacite and kyanite show a crystallographic relation to the foliation. In garnet, no change in the basic crystallographic orientation between the eclogitic and granulitic garnet composition was confirmed. However, misorientation analysis suggests a cellular microstructure not more than 1° misorientation in the core of the garnets, which is missing in the eclogitic rim indicating textural equilibration of the latter. The heterogeneous replacement patterns are characteristic for dissolution and re-precipitation reactions in an open system limited to fluid availability. The appearance of the compositional profile in garnet is interpreted as a diffusional re-equilibration step after the time-limited, fluid-mediated eclogitisation event that apparently obscured the initially sharp interface within the further retrograde metamorphic history. © 2007 Elsevier GmbH. All rights reserved.